Determination of Natural Radioactivity Levels due to Mine Tailings from Selected Mines in Southwestern Uganda - E.R, Silver Turyahabwa; Jurua, Edward; Oriada, Richard; Mugaiga, Aron; D.D., Ben Enjiku (Journal of Environment and Earth Science, 2016)
The aim of this study was to determine the natural radioactivity levels of primordial radionuclides in soil mine tailings from selected mines in Southwestern Uganda. This was achieved by analyzing thirty six samples of soil mine tailings from three mining sites using NaI(Tl) gamma ray spectrometer. The specific activity concentrations of 238U (Uranium), 232Th (Thorium) and 40K (Potassium-40) in the samples were computed. The specific activity concentrations varied from 35.5 to 147.0 Bq kg-1 for 238U, 119.3 to 376.7 Bq kg-1 for 232Th and 141.0 to 1658.5 Bq kg-1 for 40K. The outdoor absorbed dose rates in air 1.0 m above the ground level were determined. The mean absorbed dose rates for Mashonga Gold Mine, Kikagati Tin Mine and Butare Iron Ore mine were 181.2±66.8 nGy h-1, 167.2±43.0 nGy h-1 and 191.6±29.6 nGy h-1 respectively which are more than three times the world wide average value of 59 nGy h-1. The mean outdoor annual effective dose rates for the three mines were 0.37±0.14 mSv y-1, 0.34±0.09 mSv y-1 and 0.39±0.06 mSv y-1 respectively which are more than five times the world average value of 0.07 mSv y-1. Thus the mine tailings (soil) from these areas must not be used as major building material to minimize radiological hazards.
Keywords: Activity concentration; Gamma index; Soil mine tailings